The innovator's DNA mastering the five skills of disruptive innovators - Dyer, Jeff; Gregersen, Hal B. 1958-; Christensen, Clayton M. 1952-2020 (Ascent Audio, 2022)
In this bestselling book, authors Jeff Dyer, Hal Gregersen, and Clayton M. Christensen build on what we know about disruptive innovation to show how individuals can develop the skills necessary to move progressively from idea to impact. By identifying the winning behaviors of the world's best innovators, Dyer, Gregersen, and Christensen outline five discovery skills that distinguish innovative entrepreneurs and executives from ordinary managers: associating, questioning, observing, networking, and experimenting. Through real-world stories, the authors show you how to evaluate and develop your own innovator's "DNA code," including advice for how you can use the five skills to generate ideas, collaborate with colleagues to implement them, and sharpen your organization's competitive edge by building innovation skills into its culture. This innovation advantage will translate into a premium in your company's stock price-an innovation premium-which is possible only by building the code for innovation right into your organization's people, processes, and guiding philosophies. This book shows you how. Now updated with a new preface and fresh examples, The Innovator's DNA is more than ever the essential resource for individuals, managers, and teams who want to strengthen their innovative prowess
Online resource; title from title details screen (O'Reilly, viewed November 8, 2022)
Keywords: Creative ability in business; Technological innovations; Entrepreneurship; Créativité dans les affaires; Innovations; Entrepreneuriat; entrepreneurs; Audiobooks; Livres audio